The impact of carotid revascularization on cognitive function - Oliveira,Germano da Paz (2014)
The concept that carotid disease may compromise cognitive function was initially proposed by Fisher in 1951, based on an autopsy case. However, some topics involving cognitive function remain controversial, such as its correlation with carotid obstructive disease. So, the authors of this review evaluate the impact of carotid revascularization on cognitive function and the repercussions of the revascularization technique (carotid stenting vs. endarterectomy) chosen. It was clear from the literature reviewed that carotid stenosis is related to a decline in cognitive function over time. However, controversy still remains over the impact of carotid revascularization on cognitive function. With elation to the technique employed (carotid stenting vs. endarterectomy), the majority of studies found no difference between the two techniques in terms of overall cognitive outcome.